The effect of the scoring system changes in volleyball: A model and an empirical test - Kovacs, B. (Journal of Quantitative Analysis in Sports, 2009)
In 1999, the International Volleyball Federation (IVF) changed the scoring system of volleyball, from the side-out scoring system to the rally scoring system. The main goal of the scoring system change was to make the length of the game more predictable. This short paper investigates whether the change achieved its goal. First, I use a simulation model of volleyball matches to demonstrate that the length of the matches is more predictable in the rally scoring system, regardless of the relative strength of the teams. Then, I analyze data on volleyball matches from the U.S. Women's Northern Sun Intercollegiate Conference, and compare the variance of the length of the matches before and after the scoring system change in 2000 and 2001. The empirical data shows that the length of the matches became more predictable. Also, with the help of the simulation model, I show that the scoring system change does not significantly affect the outcome of the matches.